Study on the Effect of Variation in Number of Panels on Natural Frequency (International Journal of Architecture and Urbanism, 2024)
This study investigates the effect of varying the number of panels on the natural frequency and mode shape of truss bridges. Using a steel frame bridge as a case study, three different panel configurations (8, 10, and 12 panels) were analyzed through the Damped-DOF System and ABAQUS software. The results show that bridges with fewer panels exhibit lower natural frequencies, while those with more panels have higher frequencies due to increased stiffness. Furthermore, the mode shape analysis indicates that bridges with fewer panels experience greater deformations, potentially impacting their dynamic performance. This research emphasizes the importance of optimizing the number of panels in bridge design to enhance both stiffness and dynamic force resistance. Future research may explore the influence of other structural parameters on natural frequency and mode shape.